Grey Crowned Crane and Shoebills Conservation Status and Linkage to Livelihoods of Lake Victoria Shores Adjacent Communities in Mayuge District, Eastern Uganda - Nyadoi, Priscilla; Ogola, Laster S.; Kyakyo, Harriet; Tayebwa, Gilbert; Okullo, John B. L.; Aramu, Thomas (Journal of Geoscience and Environment Protection, 2020)
This research was done among communities living adjacent to Lake Victoria Shores in Mayuge District to generate knowledge on Shoebill, Grey Crowned Crane conservation status and linkage to livelihoods. This knowledge was necessary to guide design and implementation of interventions that would deliver on the species conservation and adjacent communities’ livelihood benefits at the same time. We obtained information through individual interviews with 101 members of households from targeted communities and key informers-technical officials from the district, and analysed this data using Statistical Package for the Social Sciences (SPSS) by Bryman and Cramer,(2011) Version 20. The results were then subjected to validation using focus group discussions with 10 groups of between 8 - 15 individuals representing the targeted communities and other stakeholders and the results from this further validated with ≥250 representatives of these stakeholders in a one day workshop and with evidences collected during field observations, before synthesis. The findings show: Grey Crowned Crane habitats declining due to mining, agriculture, fishing activities by adjacent communities for their livelihoods (food and income from sale of produce obtained from the species’ habitats). The communities say they need to be engaged in development and implementation of integrated interventions that will improve their livelihoods while securing conservation for Grey Crowned Cranes.
Keywords: Populations; Habitats; Bird Species; Ordinance; International Union for Conservation of Nature